An electronically controlled hydraulic power steering system for heavy vehicles. (November 2016) - Xia, Lei; Jiang, Haobin
To remedy the existing problems concerning vehicle handling for the heavy vehicle hydraulic power steering system, this article investigates a type of electronically controlled hydraulic power steering system, which can realize variable assistance characteristics and improve high-speed steering feel. To this end, a controlled electrohydraulic proportional valve is mounted in parallel with the rotary valve to regulate the flow rate through the rotary valve on demand according to vehicle speed and steering rate. After a system description in terms of structure and working principle, mathematical modeling of the electronically controlled hydraulic power steering system, vehicle, and steering resistance is conducted. To realize accurate tracking of valve spool displacement under parameter uncertainty and external disturbance, an adaptive dynamic surface control scheme is proposed for the electrohydraulic proportional valve. Numerical simulations and field tests are performed to validate the effectiveness and applicability of the electronically controlled hydraulic power steering system. The results show that the electronically controlled hydraulic power steering system can significantly improve high-speed steering feel compared with the hydraulic power steering system while maintaining the similar performance of low-speed steering portability.